2020
DOI: 10.21203/rs.2.15240/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a Postcrash First Aid Educational Program on Knowledge, Perceived Skills Confidence, and Skills Utilization Among Traffic Police Officers: A Single-Arm Before-After Intervention Study

Abstract: Background An overwhelming proportion of road traffic deaths and injuries in low- and middle-income countries (LMICs) occur in prehospital environments. Lay first responders such as police officers play an important role in providing initial assistance to victims of road traffic injuries either alone or in collaboration with others. The present study evaluated a postcrash first aid (PFA) educational program developed for police officers in Tanzania. Method A 16-hour PFA educational program was conducted in Dar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“… 36 In Tanzania, 135 police officers were assessed on their basic knowledge of post-crash FA, and the study found a low level of knowledge, with a mean score of 44.7%, but this improved to 72.9% after training, which was maintained with high confidence even after 6 months. 31 Our finding also confirms the findings of research carried out in other continents, for example in India, where major barriers to giving FA were a lack of knowledge and skills, “not knowing what to do”, and fear of legal implications. 12 The lack of skills and knowledge as a barrier could be tackled by scaling up FA training.…”
Section: Discussionsupporting
confidence: 88%
“… 36 In Tanzania, 135 police officers were assessed on their basic knowledge of post-crash FA, and the study found a low level of knowledge, with a mean score of 44.7%, but this improved to 72.9% after training, which was maintained with high confidence even after 6 months. 31 Our finding also confirms the findings of research carried out in other continents, for example in India, where major barriers to giving FA were a lack of knowledge and skills, “not knowing what to do”, and fear of legal implications. 12 The lack of skills and knowledge as a barrier could be tackled by scaling up FA training.…”
Section: Discussionsupporting
confidence: 88%
“…30 Police officers, fire fighters, and drivers are potential to be trained to give first aid, 23 as some studies had also demonstrated the efficacy of first aid training. 31,32 Acceptability reflects how emergency care and professional norms can fulfill needs from different culture and social norms. 15 In Kenya, victims were more likely to be treated faster if they dressed nicely and have financial support, indicating the issue of professional norms by health providers.…”
Section: Discussionmentioning
confidence: 99%